2015
DOI: 10.1186/s12944-015-0124-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the antioxidant role of arginine in the treatment and the protection for intralipid-induced non-alcoholic steatohepatitis

Abstract: BackgroundThis study investigated the possible roles of arginine (Arg) in ameliorating oxidative damage of intralipid (IL)-induced steatohepatitis (NASH).MethodsNASH was induced in Sprague-Dawley rats by intravenous administration of 20 % IL for three weeks and then rats were pre- and post-treated with intraperitoneal injection of Arg for two weeks. Several biochemical parameters (blood and hepatic lipid peroxidation, glutathione, glutathione peroxidase and superoxide dismutase, hepatic cytochrome P450 2El mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
0
17
1
Order By: Relevance
“…Induction of iNOS expression was associated with hepatotoxicity of other models, and its reduction was linked to hepatoprotective effect [29][30][31]. On the other hand, reduction of eNOS expression was associated with hepatotoxicity of other models, and its induction was linked to hepatoprotective effect [32][33][34]. This finding of hepatoprotective effect of nebivolol was confirmed histopathologically by improvement of diffuse liver damage occurred with APAP alone.…”
Section: Scoring Of Hepatic Enos Expression C O N T R O L a P A P A Pmentioning
confidence: 78%
“…Induction of iNOS expression was associated with hepatotoxicity of other models, and its reduction was linked to hepatoprotective effect [29][30][31]. On the other hand, reduction of eNOS expression was associated with hepatotoxicity of other models, and its induction was linked to hepatoprotective effect [32][33][34]. This finding of hepatoprotective effect of nebivolol was confirmed histopathologically by improvement of diffuse liver damage occurred with APAP alone.…”
Section: Scoring Of Hepatic Enos Expression C O N T R O L a P A P A Pmentioning
confidence: 78%
“…Arginine serves as a precursor not only in protein synthesis and the urea cycle but also in the generation of polyamines, creatine, and nitric oxide. Treatment with arginine appears to block oxidative stress–induced NASH by inhibiting cytochrome P450 2E1 activity, decreasing the TNF‐α level and restoring activities of endothelial nitric oxide synthase and antioxidant enzymes as well as glutathione levels . Previous studies have shown that treatment with betaine improved nonalcoholic fatty liver and associated hepatic insulin resistance in mice .…”
Section: Discussionmentioning
confidence: 98%
“…Treatment with arginine appears to block oxidative stress-induced NASH by inhibiting cytochrome P450 2E1 activity, decreasing the TNF-α level and restoring activities of endothelial nitric oxide synthase and antioxidant enzymes as well as glutathione levels. (33) Previous studies have shown that treatment with betaine improved nonalcoholic fatty liver and associated hepatic insulin resistance in mice. (34) Short-chain (C2, C3, C4, and C5) acyl derivatives of carnitine were positively correlated with fibrosis, whereas the precursor of carnitine, butyrobetaine, was inversely correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Arginine has antioxidant effects on NASH by inhibiting cytochrome P450 family 2 subfamily E member 1 activity and by decreasing TNF-α and antioxidant enzyme concentrations ( 107 ). Dogru et al ( 108 ) reported that increased circulating asymmetric dimethylarginine may be used as an early marker for NAFLD.…”
Section: Amino Acid Metabolism In Nafldmentioning
confidence: 99%